PHARMA DEVELOPMENT AND LAW: ARE THEY PARALLEL? - S. USHA, (International Journal of Pharma and Bio Sciences, 2016)
Intellectual Property (IP) is subject to limitations and the government can impede with the monopoly rights of the IP owners by issuing compulsory licenses, granting licenses of right and daunting with limits on the ground of public health and morality. In the pursuit called competition and development, it is forgotten that an iota of difference does matter. A general perception or what everyone considers as the seeming definition that poverty is a condition where people's basic needs for food, clothing, and shelter are not being met. But many across the globe have no access to indispensable drugs. One basic reason is of course again poverty, where, in many developing countries, consumers do not have enough purchasing power. Other important factors are inadequate national health, infrastructures and financing systems. The prices of medicines also play a vital role as many people in developing countries have to pay for their own medicines and there are no general health insurance systems. This paper addresses the concerns of patent law in pharma industry growth and its implications in developing countries.